Personalized medicine, individual choice and the common good (Cambridge University Press, 2018)
law; medicine; medico legal; bioethics and health law; ethics; philosophy
English
Keywords: Bio-ethics; Law; Medicine; Philosophy; law; medicine; medico legal; bioethics and health law; ethics; philosophy